Functional analysis of LAT3 in prostate cancer: Its downstream target and relationship with androgen receptor. Issue 9 (8th July 2021) - Rii, Junryo; Sakamoto, Shinichi; Sugiura, Masahiro; Kanesaka, Manato; Fujimoto, Ayumu; Yamada, Yasutaka; Maimaiti, Maihulan; Ando, Keisuke; Wakai, Ken; Xu, Minhui; Imamura, Yusuke; Shindo, Norihisa; et al.
Abstract: L‐type amino acid transporter 3 (LAT3, SLC43A1 ) is abundantly expressed in prostate cancer (PC) and is thought to play an essential role in PC progression through the cellular uptake of essential amino acids. Here, we analyzed the expression, function, and downstream target of LAT3 in PC. LAT3 was highly expressed in PC cells expressing androgen receptor (AR), and its expression was increased by dihydrotestosterone treatment and decreased by bicalutamide treatment. In chromatin immunoprecipitation sequencing of AR, binding of AR to the SLC43A1 region was increased by dihydrotestosterone stimulation. Knockdown of LAT3 inhibited cell proliferation, migration, and invasion, and the phosphorylation of p70S6K and 4EBP‐1. Separase ( ESPL1 ) was identified as a downstream target of LAT3 by RNA sequencing analysis. In addition, immunostaining of prostatectomy specimens was performed. In the multivariate analysis, high expression of LAT3 was an independent prognostic factor for recurrence‐free survival (hazard ratio: 3.24; P  = .0018). High LAT3 expression was correlated with the pathological T stage and a high International Society of Urological Pathology grade. In summary, our results suggest that LAT3 plays an important role in the progression of PC. Abstract : LAT3 was highly expressed in PC cells expressing androgen receptor (AR), and in chromatin immunoprecipitation sequencing of AR, binding of AR to the SLC43A1 region was increased by dihydrotestosterone stimulation. Knockdown of LAT3 inhibited cell proliferation, migration, and invasion. High expression of LAT3 was significantly associated with poor prognosis (recurrence‐free survival; P  = .0018).